Switching from one biologic to benralizumab in patients with severe eosinophilic asthma: An ANANKE study post hoc analysis - Caruso, Cristiano; Cameli, Paolo; Altieri, Elena; Aliani, Maria; Bracciale, Pietro; Brussino, Luisa; Caiaffa, Maria Filomena; Canonica, Giorgio Walter; Centanni, Stefano; D’Amato, Maria; Del Giacco, Stefano; De Michele, Fausto; et al. (Frontiers in Medicine, 2022)
Background Severe asthma is a inflammatory disease driven by eosinophilis in the majority of cases. Despite biologic therapy patients may still be sub-optimally controlled, and the choice of the best biologic is a matter of debate. Indeed, switching between biologics is common, but no guidelines are available now. Methods In this Italian post-hoc analysis , multi-center, observational, retrospective study, ANANKE, patients with severe eosinophilic asthma treated with benralizumab were divided in two groups based on history of previous biologic therapy (biologic-experienced [suboptimal response] vs naïve). Baseline clinical and laboratory characteristics were collected in the 12 months prior to benralizumab treatment. Change over time in blood eosinophils, annualized exacerbation rate (AER), asthma control (ACT), lung function and oral corticosteroid (OCS) use following benralizumab initiation were collected in the two groups. Results A total of 147 biologic-naïve and 58 biologic-experienced (34 omalizumab, 19 mepolizumab, 5 omalizumab-mepolizumab) patients were enrolled. Biologic-experienced patients were more likely to be atopic and have a higher AER despite more frequent OCS use. Similar reductions in AER (>90% in both groups), OCS use (≥49% reduction in dosage OCS), ACT improvement (≥7 points gained in 48 weeks) and lung function (≥300 mL of FEV1 improvement) were observed after benralizumab introduction within the two groups. Conclusions In this analysis, patients who were switched to benralizumab because of suboptimal control with a previous biologic therapy were more likely to be atopic and more often treated with omalizumab. Benralizumab is effective in both naïve patients and those previously treated with a biologic.